Roots Always Precede Routes: On the Road, through a Glass Darkly - Peggy PACINI (E-REA)
This article explores the subterranean layers of On the Road, firstly, approaching them from three perspectives (the dyad routes-roots, ethnogenesis and cultural geography), and secondly, considering the novel within a larger project, the “Road” project, which allows further insight into the genesis of the 1957 edition and of the original scroll published fifty years later. This article focuses on the relationship between space, identity, travel and nation, and attempts to offer a reading of the author’s French-Canadian and Franco-American invisible ethnicity as a guiding line to the On the Road proto-versions and to the themes developed (travel, mapping the land and the quest for the father[land]).